Effects of Blood Flow Restriction Training on Clinical Outcomes for Patients With ACL Reconstruction: A Systematic Review. (March 2023) - Colapietro, Mark; Portnoff, Brandon; Miller, Sayers John; Sebastianelli, Wayne; Vairo, Giampietro L.
Context: Knee muscle atrophy and weakness are common impairments after anterior cruciate ligament (ACL) reconstruction. Blood flow restriction (BFR) training represents a new approach to treat such impairments. However, limited evidence currently exists to support this intervention in related patients. Objective: To appraise literature comparing the effects of BFR training with conventional therapy on knee muscle morphological and strength properties in ACL-reconstructed patients. Data Sources: PubMed, SPORTDiscus, CINAHL, and Cochrane Central Register databases were searched for relevant articles from January 1991 through April 2021. Study Selection: Articles were minimum Level 3 evidence focusing on knee muscle morphologic as well as extensor and flexor strength outcomes in ACL-reconstructed patients of all graft types. Study Design: Systematic review. Level of Evidence: Level 2. Data Extraction: Critical appraisal instruments (Downs and Black checklist, Cochrane Collaboration tool, ROBINS-1 tool) were used to evaluate study quality. We independently calculated effect sizes (ESs) (Cohen d ) between groups in each study. The Strength of Recommendation Taxonomy grading scale was used for clinical recommendations. Results: Six articles (4 randomized control studies, 1 nonrandomized study, and 1 case-control study) met inclusion criteria. Exercises paired with BFR training included open kinetic chain, closed kinetic chain, and passive applications. Diverse assessments and time of intervention were observed across studies. ESs ranged from trivial to large in favor of BFR training for muscle morphological ( d = 0.06 to 0.81) and strength assessments ( d = −0.12 to 1.24) with CIs spanning zero. Conclusion: At this time, grade B or inconsistent and limited-quality patient-oriented evidence exists to support using BFR training to improve or maintain thigh muscle size as well as knee extensor and flexor strength in ACL-reconstructed patients. ESs indicated no consistent clinically meaningful differences when compared with conventional therapy. Subsequent analyses should be repeated as new evidence emerges to update practice guidelines.